Relazioni di Messina col Val Demone dai Normanni agli Aragonesi - Martino, Federico (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2026)
This study analyzes the relationships between Messina and the Val Demone from the Norman to the Aragonese period. In the Norman age, Messina consolidated its role as a crucial port hub for Mediterranean routes, while the Val Demone, rich in forests, provided essential resources like timber for the arsenal. The regency of Countess Adelasia marked a "Mediterranean" political orientation, fostering coexistence between the Greek-speaking element and the "Lombard" communities settled in the hinterland. A progressive intertwining of interests between the city and its territory emerges, highlighted during the crisis of 1168 when the oppida Lombardorum offered military support to the crown. A crucial moment was the concession by Henry VI (1194), which enfeoffed a vast territory to Messina, formalizing a pre-existing de facto relationship. This bond was later institutionalized by the Aragonese with the establishment of the districtus (1302 and 1357), which sanctioned Messina's political and administrative control over the Val Demone, integrating the city and the hinterland into a single geo-political entity. Hinterland; Geo-political Entity; Feudal Grant; Districtus; Lombard Communities.